2023
DOI: 10.3389/froh.2023.1223943
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral calcifying odontogenic cyst: a case report and comprehensive review of 60 years of literature

Abstract: Peripheral Calcifying Odontogenic Cyst (PCOC) is the extraosseous form of calcifying odontogenic cyst that is limited to peripheral soft tissue without bony involvement. This case report presents a case of PCOC manifested as a progressive growth of gingival mass in a young male treated with excisional biopsy. Histological examination confirmed diagnosis of PCOC with presence of characteristic ghost cells and sporadic calcifications. No recurrence of the lesion and no complication were noted at three-year follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…Discussion of research results. Evaluation of odontogenic cysts localization in various studies has generally shown a relatively similar distribution between the upper and lower jaws [28,29]. In our study, the mandible (64.03%) was more frequently affected than the maxilla.…”
Section: стоматологія / Dentistrysupporting
confidence: 63%
“…Discussion of research results. Evaluation of odontogenic cysts localization in various studies has generally shown a relatively similar distribution between the upper and lower jaws [28,29]. In our study, the mandible (64.03%) was more frequently affected than the maxilla.…”
Section: стоматологія / Dentistrysupporting
confidence: 63%